THE ROLE OF FIRM SIZE IN MODERATING THE EFFECT OF RELATED PARTY TRANSACTIONS ON FIRM VALUE - Alfonsus Rodriques Suninono; Maria Odriana Veronica Moi; Mariadriana Corysave Manehat (Jurnal Ekonomi, 2023)
This study examines the role of firm size in moderating the effect of related party transactions on firm value. This study used a sample of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) through the purposive sampling method for the 2016-2020 period, so the final sample number was 10, with a total of 50 observations. Hypothesis testing used panel data regression with eviews version 12. Study results show that sales-related party transactions have a positive and significant effect on firm value, while purchased-related party transactions do not affect on firm value. The results of the moderation effect study show that company size cannot moderate the relationship between sales related party transactions and purchased related party transactions on firm value.